Development of a robust throughput process for the production of PMMA membranes via a TIPS air casting method - Murphy, Niall (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Lateral flow membranes (membranes that allow movement of fluid across the membrane rather than through it) play a crucial role in the functionality of immunoassay devices determining performance speed and assay reliability. These devices are increasingly important, being used for an expanding range of point-of-care diagnosis in healthcare. Nitrocellulose has been the polymer predominantly used for membrane fabrication for these devices, but its instability and tendency to spontaneously decompose at a higher temperature, as well as inconsistent properties of the cellulose used as the raw feedstock, are drawbacks. Synthetic polymers have the potential to reduce the chances of material failure and the production of more reliable and reproducible membranes for this highly significant application field. Poly(methyl methacrylate) (PMMA) is one such polymer. It has previously been demonstrated that PMMA membranes with good thermal stability can be produced, and have potential for protein binding, which is a key attribute for materials suitable for use in immunoassay devices. However, the literature on PMMA membranes produced via air casting or other techniques is scarce and there are few demonstrations of lateral flow capability. The aim of this study was to develop a repeatable and robust methodology for production of PMMA membranes using an air casting approach with thermally induced phase separation (TIPS) of the polymer. A casting rig was designed and optimised for successful production of PMMA membranes on a commercial backing material. The influence of polymer loading, water content, and humidity on the PMMA membrane characteristics were also investigated. In addition, the effects of glycerol and poly(ethylene glycol) as individual additives on the membrane integrity and pore morphology were studied. The results show that the membrane morphology can be tailored by controlling the composition of the lacquer used for casting and the process parameters.
APPROVED
Keywords: TIPS, Aircast, Membrane, PMMA, Lateral flow, Immunoassay